Coconut Picking Workers (Pabaruak) In Nagari Lareh Nan Panjang Districts Vii Koto Sei. Sariak Districs Padang Pariaman - Apriani Apriani; Yoskar Kadarisman (Peneliti.net, 2023)
This research was conducted in Nagari Lareh Nan Panjang, District VII Koto Sei. Sariak Padang Pariaman Regency with the aim of knowing the Forms of Social Action from Coconut Pickers (Pabaruak) in Nagari Lareh Nan Panjang. This study uses a descriptive qualitative research method. In collecting data using observation research methods, in-depth interviews and also documentation. The theory used is the theory of Social Action from the character Max Weber in Wirawan's book which consists of Social Facts, Social Definitions, and Social Behavior. The results of this study are that the actions taken by the people of Nagari Lareh Nan Panjang who work as coconut pickers (Pabaruak) are included in the form of Instrumental Rational Action in the theory of social action in the character of Max Weber.